DESIGN OF ELECTRONIC FILING SYSTEM USING IMAGEWARE SCAN MANAGER IN BANK BJB KCP SAMARANG - Audry Putri Ramadhany (Ebiz Prima Nusa, 2023)
The archive system at Bank BJB KCP Samarang was initially not optimal, as evidenced by several problems that arise because of archives, such as the length of time for finding archives, archives are not neatly arranged, and there is no archive lending system. This can interfere with the work of employees. This project aims to design an electronic filing system at Bank BJB KCP Samarang using ImageWare Scan Manager. The work procedures carried out included applying for permits, interviews, identifying problems, designing programs, making programs, testing, evaluating, and finally making a manual for handling archives. The result of this archival system design is that the archive storage system used is a subject archive storage system based on the name of the credit lending category and a chronological storage system based on the year of the archive, as well as electronic archive storage using the four existing structures in the application, namely workgroups, worksheet templates, worksheets, and fields. For archive storage procedures there are four stages, namely login workgroup, open worksheet, index data, and import documents. Furthermore, the recovery of archives is carried out in four stages, namely requesting, searching, finding, and recording borrowed archives. Based on the results of tests using alpha beta testing, no errors were found and can facilitate archive discovery and facilitate work, so this application can be used as an alternative in archive storage.